'The Phonetic Structure of a Cypriotic Dialect': a rediscovered paper by J. R. Firth - Coleman, J (Blackwell Publishing, 2006)
The Philological Society President and Secretary's Annual Report for 1937 (Braunholtz & Woodward 1938) reports that J. R. Firth read a paper on 'The Phonetic Structure of a Cypriotic Dialect' to the meeting of the Society on 29 May 1937. Firth's paper was never published, and its very existence was subsequently forgotten. Happily, a manuscript and handout for the lecture as well as copious background notes relating to the study have recently come to light at the School of Oriental and African Studies, London. Though somewhat incomplete, much of the content of the paper can be pieced together to yield a surprising new addition to the body of Firth's work.